2006
DOI: 10.1016/j.jacc.2005.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Is Brain Natriuretic Peptide Production Decreased in Obese Subjects?

Abstract: Both obesity and heart failure (HF) are highly prevalent syndromes in modern Western society. Nearly 60% of the U.S. population has a body mass index (BMI) Ͼ25 kg/m 2 (1). The incidence of HF approaches 10 per 1,000 among persons older than 65 years (2). Because both syndromes are highly prevalent, patients are likely to have both simultaneously.Surprisingly, obese HF patients have a better prognosis than normal-weight HF patients, giving rise to the so-called obesity paradox (3).Brain natriuretic peptide (BNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 12 publications
1
33
0
3
Order By: Relevance
“…To our knowledge, 14 studies have investigated the effect of obesity on BNP and NT-proBNP concentrations. Six studies investigated the relationship between BNP and BMI (12)(13)(14)(15)(16)(17), 2 studies correlated obesity with NT-proBNP (18 -20 ), and 6 others included both BNP and NT-proBNP (7,18,(21)(22)(23)(24). Of the 12 studies that assessed BNP concentrations, 11 found reduced concentrations in obese and overweight patients; a single study showed that BNP concentrations were unaffected by BMI (21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, 14 studies have investigated the effect of obesity on BNP and NT-proBNP concentrations. Six studies investigated the relationship between BNP and BMI (12)(13)(14)(15)(16)(17), 2 studies correlated obesity with NT-proBNP (18 -20 ), and 6 others included both BNP and NT-proBNP (7,18,(21)(22)(23)(24). Of the 12 studies that assessed BNP concentrations, 11 found reduced concentrations in obese and overweight patients; a single study showed that BNP concentrations were unaffected by BMI (21 ).…”
Section: Discussionmentioning
confidence: 99%
“…A problem with this hypothesis, however, is that NTproBNP concentrations are also reduced in obesity, although this inactive cometabolite is not cleared by the NPR-C mechanism (12,18,20,22,23 ). Further, van Kimmenade et al (24 ) showed in an interventional study of 22 patients who had undergone surgical treatment for obesity that a decrease in BMI is accompanied by increased concentrations of both BNP and NTproBNP. These data suggest a relationship between adipose tissue and the production of both peptides.…”
Section: Discussionmentioning
confidence: 99%
“…After 52 weeks, BMI had decreased by 20% and BNP levels had nearly doubled 59. The exact mechanism for this is unclear, but recent studies suggest decreased production is the cause 60. Despite lower levels of natriuretic peptides in the obese patient, circulating levels can still be used for prognosis 61…”
Section: Natriuretic Peptides In Obesitymentioning
confidence: 99%
“…Furthermore, renal dysfunction is associated with elevated concentrations of BNP markers [17] and BNP also has a negative correlation with body mass index (BMI) [18,19]. Taken together, these data suggest that HF management could benefit from additional assessment of cardiac muscle health independent of volume status.…”
Section: Introductionmentioning
confidence: 90%
“…In this manner, CS could assist with management of complex, multi-organ disease syndromes. Conversely, patients with obesity may have false negative BNP, yet with failing heart muscle [19]. CS in this instance would help identify the failing heart muscle.…”
Section: Implication Of Cs For Population Healthmentioning
confidence: 99%